Comparative Study of The Dynamics of Riba Discourses Between Sharia Banks and Conventional Banks - Ganjar Eka Subakti; Muhammad Rindu Fajar Islamy (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to explore the comparison of views among banking practitioners in the dynamics of usury discourse. Lately, the trend of "hijrah" among the millennial generation is increasingly popular, and their increasing interest in watching da'wah messages conveyed by clerics on social media. The issue of 'avoiding usury' is one of the targets for the delivery of da'wah by agents; this is related to the prohibition of the practice of usury by religion based on texts from both the Koran and Hadith. However, understanding usury viewed from only one point of view can potentially lead to misunderstandings, especially studies that discuss usury at this time are still 'puzzle pieces,' not comprehensive, how the discussion of the depth of the problematics of usury becomes one of the most urgent matters for further review. This research study uses a qualitative approach, where data collection techniques are carried out through structured interviews, observation, and documentation. Analysis of the data in this study using the theory of Miles and Huberman. The research subject focuses on one key informant, namely a banking practitioner who has been in this world for a long time. The research results show that there are different basic principles between Islamic banks and conventional banks in highlighting the problem of the concept of usury